MODELING OF THE MONITORING SYSTEM OF LEARNING OUTCOMES IN ADULT EDUCATION - Nevdakh, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In recent years, the need has arisen for a change in conceptual approaches to the phenomena of “monitoring” and “assessment” of learning outcomes in adult education. The ultimate goal of monitoring should be to strengthen and achieve a high level of responsibility of the learners for the process and outcomes of their education. The purpose of the research is to create a model of the monitoring system of learning outcomes in adult education and to describe a methodology for implementing alternative methods of monitoring. Research methods: a theoretical analysis of the concept of “monitoring”, generalization and systematization of approaches to monitoring, analysis of the characteristics of adult education, modeling of the monitoring system of learning outcomes in adult education, ranging monitoring types by teachers, analysis of the results of the empirical research. The main results of the research: a model of the monitoring system oflearning outcomes in adult education includes preparatory, practical and analytical stages and it is built taking into account the purpose, content, methods of pedagogical communication, means, timing and duration of control. It also includes traditional and alternative ways of monitoring learning outcomes with guidelines for their use in adult education.